Can nasal Staphylococcus aureus screening and decolonization prior to elective total joint arthroplasty reduce surgical site and prosthesis-related infections? A systematic review and meta-analysis - Xingyang Zhu; Xiaobo Sun; Yuqing Zeng; Wenjun Feng; Jie Li; Jianchun Zeng; Yirong Zeng (Journal of Orthopaedic Surgery and Research, 2020)
Abstract Background Nasal Staphylococcus aureus (S. aureus) screening and decolonization has been widely used to reduce surgical site infections (SSIs) prior to total knee and hip arthroplasty (TKA and THA). However, it remains considerably controversial. The aim of this study was to ascertain whether this scheme could reduce SSIs and periprosthetic joint infections (PJIs) following elective primary total joint arthroplasty (TJA). Methods A systematic search was performed in MEDLINE, Embase, and the Cochrane Library until October, 2019. Outcomes of interest included SSI, PJI, superficial infection, and different bacterial species that caused infections. Data from eligible studies were then extracted and synthesized. Pooled odds ratios (OR) and 95% confidence intervals (CIs) were calculated. We also performed additional analyses to evaluate whether there were differences in postoperative SSIs caused by S. aureus or other bacteria. Results Nine studies were included in our meta-analysis. The pooled data elucidated that nasal S. aureus screening and decolonization dramatically mitigated the risk of SSI, PJI, and superficial infection compared to nondecolonization group. The analysis of bacterial species causing infection also showed that the S. aureus infections postoperative were significantly decreased in the decolonization group. However, there was no statistical difference in the SSI caused by other bacteria between the two groups. Conclusion S. aureus screening and decolonization prior to elective primary THA and TKA could significantly decrease the risk of SSI and PJI. However, more robust studies are needed to further evaluate the impact of S. aureus screening and decolonization on infection risk after TJA.